Territorial Governance/Instances of Governance for Tourism Development in the Serras e Lago tourist region in Tocantins (Research, Society and Development, 2022)
In this article, the focus of considerations turns to the contour of the tourist region of Serras e Lago in the state of Tocantins and the importance of the performance of governance instances for regional tourism in the face of domestic tourism opportunities. The State of Tocantins has an expressive vocation for adventure tourism, cultural tourism and ecotourism. The segments are directly related to the principles of environmental, social and economic sustainability. Domestic tourism in Brazil has found significant opportunities in light of the sanitary conditions caused by COVID-19. The Ministry of Tourism reveals the increase in demand for national destinations to the detriment of international destinations. With this, tourist regions still little explored find alternatives to boost the development of the activity. However, the need for planning, organization and monitoring become a condition for the realization of alternatives. In this context, the role of governance instances assumes a leading role. To navigate the sea of opportunities identified by domestic tourism in Brazil, the state of Tocantins needs to position itself in an organized and planned manner to develop its potential associated with the management and performance of future and current governance instances.